The mobilization of computerized crime mapping: a randomized controlled trial - Taniguchi, Travis A. (Journal of experimental criminology, 2019)
To develop and evaluate the effectiveness of a decentralized, smartphone-based crime mapping and analysis tool designed for law enforcement officers working in a patrol capacity.